2022
DOI: 10.1155/2022/6794018
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Main Movement Characteristics of Hip Hop Dance Based on Deep Learning of Dance Movements

Abstract: In order to explore the main action characteristics of hip hop dance, a deep learning recognition system based on dance action is proposed. The network is based on convolution, pooling, and full connection calculation in a convolutional neural network (CNN). On the one hand, the pixel information in the video frame is extracted as the network input feature in the spatial domain. On the other hand, in the time domain, in order to better represent the change characteristics of video actions, optical flow informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Dancers are able to explore new avenues for movement and self-expression through technology, the way it is through interactive applications, digital designs and experiences. Such enhances their creative practice and assist to develop greater connections with their profession [10][11]. Dancing instruction might be revolutionized by including emotion detection into the curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…Dancers are able to explore new avenues for movement and self-expression through technology, the way it is through interactive applications, digital designs and experiences. Such enhances their creative practice and assist to develop greater connections with their profession [10][11]. Dancing instruction might be revolutionized by including emotion detection into the curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%